The Prevalence and Characteristics of Emergency Medicine Patient Use of New Media - Post, Lori Ann; Vaca, Federico E; Biroscak, Brian J; Dziura, James; Brandt, Cynthia; Bernstein, Steven L; Taylor, Richard; Jagminas, Liudvikas; D'Onofrio, Gail (JMIR Publications, 2015)
BackgroundLittle is known about "new media" use, defined as media content created or consumed on demand on an electronic device, by patients in emergency department (ED) settings. The application of this technology has the potential to enhance health care beyond the index visit. ObjectiveThe objectives are to determine the prevalence and characteristics of ED patients' use of new media and to then define and identify the potential of new media to transcend health care barriers and improve the public's health. MethodsFace-to-face, cross-sectional surveys in Spanish and English were given to 5,994 patients who were sequentially enrolled from July 12 to August 30, 2012. Data were collected from across a Southern Connecticut health care system's 3 high-volume EDs for 24 hours a day, 7 days a week for 6 weeks. The EDs were part of an urban academic teaching hospital, an urban community hospital, and an academic affiliate hospital. ResultsA total of 5,994 (89% response rate) ED patients reported identical ownership of cell phones (85%, P<.001) and smartphones (51%, P<.001) that were used for calling (99%, P<.001). The older the patient, however, the less likely it was that the patient used the phone for texting (96% vs 16%, P<.001). Income was positively associated with smartphone ownership (P<.001) and the use of health apps (P>.05) and personal health records (P<.001). Ownership of iPhones compared to Android phones were similar (44% vs 45%, P<.05). Race and ethnicity played a significant role in texting and smartphone ownership, with Hispanics reporting the highest rates of 79% and 56%, respectively, followed by black non-Hispanics at 77% and 54%, respectively, and white non-Hispanics at 65% and 42%, respectively (P<.05). ConclusionsThere is a critical mass of ED patients who use new media. Older persons are less comfortable texting and using smartphone apps. Income status has a positive relationship with smartphone ownership and use of smartphone apps. Regardless of income, however, texting and ownership of smartphones was highest for Latinos and black non-Latinos. These findings have implications for expanding health care beyond the ED visit through the use of cell phones, smartphones, texting, the Internet, and health care apps to improve the health of the public.